EVALUASI PROGRAM PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) DALAM MEMBENTUK KARAKTER TANGGUNG JAWAB SISWA DI SDN BLOTONGAN 02 SALATIGA - Asari, Ariya; Mawardi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the success of the P5 program in forming students' responsible character using the Goal Oriented Evaluation (GOE) evaluation model. The approach used is descriptive qualitative with the research subjects being principals, teachers, and students, which are determined through purposive sampling techniques. Data collection techniques include interviews, observations, and documentation. The results of the study indicate that the P5 program is quite successful in instilling students' responsibility values ​​through activities with local wisdom and religious themes that are designed according to the social context of students. Students show increased discipline, ability to complete tasks, and a sense of concern for the school environment and family. This success is due to the active role of teachers as facilitators, the involvement of the principal in directing the implementation of the program, and routines that are applied consistently. The main obstacles are the lack of teacher experience in designing meaningful projects, time constraints, and differences in student maturity levels. In general, the GOE evaluation model has proven effective in evaluating the achievement of P5 program objectives objectively and in a focused manner, and provides a basis for future program improvements.